Abundancia y fluctuaciones de aves limícolas (Charadriiformes) en una playa fangosa de Chomes, Costa Rica - Barrantes Montero, Gilbert (1992)
We recorded 27 species of Charadriiformes on the mud flats of Chomes, Golfo de Nicoya, Costa Rica, during biweekly censuses over one year. These were grouped taking into account their abundance and permanence on the flat. The first cluster was formed by Pluvialis squatarola, Numenius phaeopus, Charadrius wilsonia and Cataptrophorus semipalmatus which showed high abundance and were present on the flat throughout the year. The second cluster includes Charadrius semipalmatus, Limnodromus griseus, Calidris mauri, and Arenaria interpres. These were abundant, and all individuals migrated to North America during the reproductive season. Sterna maxima, S. sandvicensis and S. antillarun were abundant albeit for short period. The third group includes species of low abudance. The number of species and the number of individuals probably fluctuated due to migration or movements between neighbouring beaches.